Pain without reward: A phenomenological exploration of stillbirth for couples and their hospital encounter. Issue 2 (7th February 2021) - King, Michael Q.; Oka, Megan; Robinson, W. David
Abstract: Stillbirth constitutes a unique form of grief related to the death of an unborn child. This study explores the experiences of eight couples who lost a child to stillbirth, from the time they suspected something was wrong to their release from the hospital and beyond. Couples were interviewed conjointly and data were analyzed qualitatively using a phenomenological approach. Analysis revealed themes of positive and negative encounters with hospital staff, grief and loss, relationships with spouse and family, and long-term impacts. Implications for clinicians are discussed, including gender differences in the grief process for fathers and mothers.